GAMBARAN PERILAKU PENCARIAN PENGOBATAN TERHADAP KEJADIAN DERMATITIS KONTAK PADA PETANI GARAM (STUDI PADA PETANI GARAM KECAMATAN KALIORI, KABUPATEN REMBANG) - Wahyuni Christiany Br Sinaga; Henry Setyawan Susanto; Ari Udijono; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dermatitis is an inflammation of epidermis and dermis provides subjective symptoms of itching resulting a growing and diverse rash. Based on Riskesdas 2007, prevalence of dermatitis in Indonesia was 67.8%. District Health Office Rembang dermatitis including five major diseases, prevalence was 16.9%. In Kaliori including big five 23.3%. The purpose this study was describe health seeking behavior of contact dermatitis in the salt farmer in District Kaliori and related factors. This study used descriptive research with cross-sectional study design. The study populations were all salt farmers who suffered from contact dermatitis. The samples of this study were 87 people. The results pattern of health seeking behavior was self-medication (50,6%), check to health worker (26,4%), and did not do anything because did not want (23%). Respondents who did self-medication knowledge were poor (63.6%). The average age was 57 years old, education finished primary school (60,9%), income above UMR (56,3%). Perceived susceptibility, which felt susceptible 58.6%, but who did self-medication felt susceptible 63.9%. Perceived severity, which felt severe 51.5%, but who did self-medication felt not worse 54.8%. Perceived benefits, who feel a benefit 59.8%, but who did self-medication felt no benefit. Perceived barriers, which felt there was a barriers 50.6%, which check to health workers felt there was a barriers 38.6%. Respondents with good support 52,9%, have health care 52,9%, access of health service far 70,1%. It was suggested that primary health care of Kaliori will increase knowledge and awareness of salt farmers about contact dermatitis and appropriate treatment.